The acquisition system of experimental data for Uragan-2M - Gubarev, S.P.; Opaleva, G.P.; Taran, V.S.; Zolototrubova, M.I. (Вопросы атомной науки и техники, 2011)
The data acquisition system for controlling the real-time parameters of high-temperature plasma for Uragan-2M device has been presented. Its development is carried out in Kharkov Institute of Plasma Physics of NSC KIPT. This system provides synchronous multi-channel high-speed measurement of electrical signals coming from installed sensors and diagnostic equipment as well as collecting and displaying information, archiving it on a server and electronic data depository allowing users to access files with recorded data.